Pengaruh Latihan Isokinetik Mirip dengan Performa terhadap Pengembangan Kekuatan Kaki dan Prestasi Lompat Jauh Putri - Ansam Khazaal Jabbar; Abdullah Shanta Faraj (Indonesian Journal of Physical Education and Sport Science, 2025)
Study purpose. This study aims to identify the effect of Isokinetic similar to performance exercises to develop legs muscular strength and achievement of female long jump, women have less muscle mass, therefore less strength, so the strength level of female athletes must be developed in various ways, including using isokinetic exercises. Materials and methods. The research method using experimental was used the experimental design of random selection equivalent groups with pre- and post-observation, Researcher selected sample intentionally, The research community was composed of (9) national team long jumpers. The sample was selected with (8) players, and (1) player was excluded due to her high achievement of 5 m., which affects homogeneity and equality. The validity and reliability of instruments rely on extracted coefficient of self-truthfulness, and by test and retest to inform tests stability. Results: Results of research showed that isokinetic exercises similar to performance have a positive effect on level of achievement among female long jump players, which were represented in physical variables and level of achievement, and that there were in variables of physical abilities and level of achievement, where they excelled. Conclusion. Concluded that experimental group that used Isokinetic similar to the performance exercises achieved the training objects in developing the muscular strength and achievement of female long jump. Accordingly, it was recommended the adoption of exercises Isokinetic similar to the performance as it achieved the training objects in developing legs muscular strength and achievement of female long jump.